Social well-being in Malaysia from the Islamic and conventional perspective - Jaafar, Samsuddin; Mohamed Osman, Mariana; Bachok, Syahriah (IIUM Press, 2018)
This research intends to model subjective sustainable well-being [SSWB] model for Malaysia as complimentary social indicators to Malaysia Well-Being Index [MWI]. Typical gap found in reports by government agencies on well-being was the need to understand what may have affected the nations’ subjective well-being [SWB]. Additionally, by incorporating Maslow’s Theory of Hierarchy of Needs, the research also determines if the HIH and HIE are affected by levels of human needs. This research delivers its novelty by acknowledging the citizens as the causal agent to their SSWB being instead of the outcome of resources provision or policy implementation to enhance well-being. The SSWB model is valuable for measuring the readiness and social progress of Malaysians to embrace sustainability in well-being throughout their lifestyle. The research delivers beneficial findings for policy review, which, hitherto, was difficult to evaluate due to the lack of quantifiable subjective data in MWI.